EFEKTIFITAS PENGEMBANGAN STRATEGI PENGELOLAAN SUROBOYO BUS - Arini Sulistyowati; Supra yoga (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to identify and describe the development of an effective Suroboyo Bus management strategy. This research uses a qualitative approach. Data collection is done by interviews, documentation, and questionnaires. Informants in this study were the public as Suroboyo Bus passengers, the Head of Operations Manager at Suroboyo Bus in Surabaya Transportation Department and the Head of Trash Management on Suroboyo Bus in the Surabaya City Green Cleaning and Open Space Office, and the Suroboyo Bus Organizer. Data analysis techniques using SWOT. The results in this study indicate that there are weaknesses and threats that can be overcome by using the strengths and opportunities that Suroboyo Bus has to develop. In this case, future strategies based on digital technology are formulated by implementing Excellent Public Service based on Digital Technology. In implementing the strategy, the focus is more on the use of digital technology to provide satisfying services to Suroboyo Bus users.